The Urgency and Importance of an Active Information Seeking Task Influence the Interruption of Information Encountering Episodes - Wildemuth, Barbara M. (Evidence Based Library and Information Practice, 2020)
A Review of: Makri, S., & Buckley, L. (2020). Down the rabbit hole: Investigating disruption of the information encountering process. Journal of the Association for Information Science and Technology, 71(2), 127–142. https://doi.org/10.1002/asi.24233 Abstract Objective – To understand when and why information encountering episodes are interrupted. Design – Naturalistic observational and interview study. Setting – Personal network of the study authors in London. Subjects – Fifteen personal contacts of authors, aged 22-60, recruited via word-of-mouth and social media. Methods – Each participant was asked to conduct a search on a self-chosen topic. The researchers took notes and recorded search interactions and think-aloud protocols. After the search, a follow-up interview asked whether the participant had unexpectedly encountered any interesting or useful information; if so, the researchers asked for more details about that episode. If not, they conducted a critical incident technique interview, focused on a memorable example of a past information-encountering episode. The researchers used inductive thematic analysis to analyze the data, augmented with constant comparison across the data and the themes to ensure analytical rigor. Main Results – The most frequent point at which participants interrupted an information encountering (IE) episode was near its beginning, when the searcher noted an information stimulus but then immediately returned to the active information-seeking task. IE episodes were also interrupted 1) after the searcher examined the encountered content but did not explore it further, and 2) after the searcher explored it but decided it was not useful. The factors that influenced interruptions of IE episodes included the searcher’s reluctance to invest the time and effort needed to engage with the encountered information, due to the importance or urgency of the active information-seeking task; the searcher’s reluctance to leave the active information-seeking task, seeing IE as a distraction from that task; the searcher’s reluctance to multitask, i.e., to keep track of both the IE episode and the active information-seeking task; the searcher’s reluctance to risk a dead end; the searcher’s reluctance to be seduced by the “shiny thing” of encountered information (p. 136) and to drift too far away from the active information-seeking task; and the searcher’s reluctance to get “caught up” emotionally in the IE episode (p. 138), a “temptation that is satisfying only in the short-term” (p. 138). Conclusion – Overall, the results help us understand when and why disruption of IE can occur. When an IE episode begins, the searcher is not able to estimate the time and effort required to pursue it or the fruitfulness of following it through. Thus, factors associated with the primary information-seeking task (e.g., its importance or urgency) and with the searcher (e.g., ability to multitask) tend to influence decisions about when to interrupt an IE episode.